Strategies for self sustainability of heritage in the rural environment - Fernández Ortea, Javier (2017)
The spanish heritage is located predominantly in rural areas, however, it has not been subject to the same attention as its urban neighbor. Enhancing the archaeological, historical, culinary, ethnological legacy is to boost rural areas. The new profession of cultural manager must create active strategies that connect the territory, heritage and visitors. The Management Plan is the starting point for the outlining of active policies on the resources and its recipients for the conservation and sustainable use of heritage.